The emergence and development of the right of privacy in the United States (Revista do Tribunal Regional Federal da 3ª Região, 2015)
The article discusses the emergence and evolution of the right of privacy in the United States. It analyzes the publication of Warren and Brandeis and its influence in doctrine, case law and legislation. It examines the doctrinal constructions subsequent to the article of Warren and Brandeis, such as the studies of Prosser and Bloustein. It seeks to trace the differences between the right of privacy and right of publicity, as well as the formulation of the constitutional privacy. Finally, it examines the relationship between the personality rights and the right of privacy.
Keywords: personality rights; human dignity; Commom Law; right of privacy; right of publicy